Incipient miscommunication as a resource in international negotiations - Öberg, Britt-Marie (HERMES - Journal of Language and Communication in Business, 2017)
This paper presents a categorization of sequences of incipient miscommunication according to their sources and to how they are indicated, thematized and solved in cross-cultural negotiating activities between native and non-native speakers of English. It was found that cross-cultural miscommunicative instances were an intrinsic part of the establishing of consensus and therefore they could be used as a communicative resource. Moreover, the importance of the problems presented by the issues at hand overrides the significance of the problems presented by the participants’ language inadequacies. However, miscommunication related to differences in socio-cultural background and to divergent degrees of unawareness regarding the miscommunication often has more serious interactional consequences than a varying or insufficient language proficiency.